Relationship of lemongrass decoction administration on perineal wound healing - Elmi Puji Pangestu; Zulliati; Dwi Sogi Sri Redjeki; Lisda Handayani (Health Sciences International Journal, 2026)
Background: Perineal wounds are a common childbirth complication that significantly impacts maternal quality of life. In resource-limited settings such as plantation clinics, effective, safe, and affordable solutions are needed. Lemongrass decoction as a traditional application holds potential as complementary therapy, but empirical evidence for postpartum perineal wounds remains limited. Objective: To determine the relationship between the administration of lemongrass decoction and the healing of perineal wounds in postpartum mothers at the PT. GSPP Polyclinic. Methods: A quasi-experimental study with a non-equivalent control group design was conducted on 20 postpartum mothers divided into intervention and control groups. The intervention group received standard care plus topical application of lemongrass decoction twice daily, while the control group received standard care only. Wound healing was assessed based on clinical time (≤6 days for the 'Good' category) up to day 7. Data analysis used Fisher's Exact test and Odds Ratio (OR) calculation. Results: Most mothers who received lemongrass decoction (9 out of 10) experienced good healing (<6 days), while the majority who did not receive the intervention (7 out of 10) experienced poor healing (≥6 days). The relationship was statistically significant (p=0.020). Mothers who did not receive lemongrass decoction therapy had 21 times higher odds of experiencing poor healing (OR = 21.000; 95% CI: 1.777-248.103). Conclusion: The administration of lemongrass decoction has a significant and protective relationship with the acceleration of perineal wound healing in postpartum mothers.